2014
DOI: 10.1002/ajh.23844
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine function and bone disease during long‐term chelation therapy with deferasirox in patients with β‐thalassemia major

Abstract: *Iron overload in b-thalassemia major (TM) typically results in iron-induced cardiomyopathy, liver disease, and endocrine complications. We examined the incidence and progression of endocrine disorders (hypothyroidism, diabetes, hypoparathyroidism, hypogonadism), growth and pubertal delay, and bone metabolism disease during long-term deferasirox chelation therapy in a real clinical practice setting. We report a multicenter retrospective cohort study of 86 transfusion-dependent patients with TM treated with onc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 22 publications
1
58
2
Order By: Relevance
“…Various studies have shown that children with thalassemia major suffer from growth retardation, impaired immune function, and low body mass index [810]. The above treatment-related complications disrupt the balance between osteoblasts and osteoclasts by interfering with various molecular mechanisms leading to osteoporosis and increased fracture risk during adulthood [11, 12]. Chelation treatment should be added routinely in order to prevent iron overload and its toxic effects [12, 13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various studies have shown that children with thalassemia major suffer from growth retardation, impaired immune function, and low body mass index [810]. The above treatment-related complications disrupt the balance between osteoblasts and osteoclasts by interfering with various molecular mechanisms leading to osteoporosis and increased fracture risk during adulthood [11, 12]. Chelation treatment should be added routinely in order to prevent iron overload and its toxic effects [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…The above treatment-related complications disrupt the balance between osteoblasts and osteoclasts by interfering with various molecular mechanisms leading to osteoporosis and increased fracture risk during adulthood [11, 12]. Chelation treatment should be added routinely in order to prevent iron overload and its toxic effects [12, 13]. However, parenteral administration of chelate agents reduces patients' compliance and the longer survival rates lead to some degree of toxic systemic iron overload.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, deferasirox use was not associated with growth failure (Supporting Information Fig. 3) [1,5,6]. This was truer when it was started during childhood, likely because other factors such as early hypophyseal damage with abnormal release of sexual hormones may compromise normal growth during adolescence independent of the use of deferasirox.…”
Section: Deferasirox and Children: From Clinical Trials To The Real Wmentioning
confidence: 99%
“…Despite the fact that rituximab in combination with chemotherapy has proven to increase FL progression free and overall survival, there is considerable inter-individual variability in the clinical response to this anti-CD20 monoclonal antibody (MAb) [2]. Apoptosis induction seems to be a process involved in the mechanism of action of MAbs [2][3][4] and several studies have reported the association of polymorphisms in genes coding for apoptotic extrinsic pathway proteins, such as death receptors and their ligands, with susceptibility to lymphomas or immunotherapy response [5,6]. However, there are no studies analyzing the relationship between polymorphisms in genes coding for extrinsic apoptosis inducers and rituximab response.…”
Section: A Polymorphism In Fasl Is Associated With Rituximab Responsementioning
confidence: 99%